Bakuman. 2, Chocolate and akamaru - Ōba, Tsugumi; Obata, Takeshi, 1969-; Miyaki, Tetsuichiro (San Francisco : VIZ Media, 2010)
Moritaka and Akito, having teamed up to write manga, try and get the attention of a publishing house, but are concerned they will not have what it takes to impress an editor.
Translated from the Japanese.
"First published in Japan in 2008 by Shueisha Inc., Tokyo"--P. facing t.p.
"This book reads from right to left" --Cover p. [4].
Young Adult
Young Adult
Keywords: Artists -- Comic books, strips, etc. -- Fiction; Comic books, strips, etc. -- Japan -- Comic books, strips, etc. -- Fiction; Drawing -- Comic books, strips, etc. -- Fiction; Artists -- Comic books, strips, etc. -- Fiction; Manga -- Comic books, strips, etc. -- Fiction; Drawing -- Comic books, strips, etc. -- Fiction; Manga; Comic books, strips, etc; Graphic novels; Graphic novels